Dysregulation of Neuronal Iron Homeostasis as an Alternative Unifying Effect of Mutations Causing Familial Alzheimer’s Disease - Lumsden, Amanda L.; Rogers, Jack T.; Majd, Shohreh; Newman, Morgan; Sutherland, Greg T.; Verdile, Giuseppe; Lardelli, Michael (Frontiers in Neuroscience, 2018)
The overwhelming majority of dominant mutations causing early onset familial Alzheimer’s disease (EOfAD) occur in only three genes, PSEN1, PSEN2 and APP. An effect-in-common of these mutations is alteration of production of the APP-derived peptide, Amyloidbeta (Abeta). It is this key fact that underlies the authority of the Amyloid Hypothesis that has informed Alzheimer’s disease research for over two decades. Any challenge to this authority must offer an alternative explanation for the relationship between the PSEN genes and APP. In this paper, we explore one possible alternative relationship – the dysregulation of cellular iron homeostasis as a common effect of EOfAD mutations in these genes. This idea is attractive since it provides clear connections between EOfAD mutations and major characteristics of Alzheimer’s disease such as dysfunctional mitochondria, vascular risk factors/hypoxia, energy metabolism and inflammation. We combine our ideas with observations by others to describe a “Stress Threshold Change of State” model of Alzheimer’s disease that may begin to explain the existence of both EOfAD and late onset sporadic (LOsAD), forms of the disease. Directing research to investigate the role of dysregulation of iron homeostasis in EOfAD may be a profitable way forward in our struggle to understand this form of dementia.